Finding space for rewilding: Nature futures scenarios reveal ecological opportunities based on plural values of nature from participatory processes - Laura C. Quintero-Uribe; Henrique M. Pereira; Rowan Dunn-Capper; Jenny Schmidt; Néstor Fernández (PLoS ONE, 2026)
Ecological restoration is increasingly emphasised by ambitious biodiversity policies as essential for reversing ecosystem degradation in human-dominated landscapes. Among restoration approaches, rewilding fosters self-sustaining ecological processes and reduces the need for direct human intervention. However, effective implementation requires careful evaluation of co-benefits and trade-offs with local communities’ interests. This underscores the urgent need for participatory processes that align restoration efforts with local contexts. This study operationalised the Nature Futures Framework, a participatory, value-based scenario-planning methodology, to co-develop rewilding scenarios with local rewilding experts. To assess trade-offs and co-benefits, relevant stakeholders were systematically identified using Net-Map analysis. Semi-structured interviews and participatory mapping were used to assess stakeholder perceptions and the feasibility of translating scenario narratives into rewilding actions. The three scenarios articulated distinct priorities. The Nature for Nature scenario prioritised restoring landscape connectivity and promoting natural succession toward old forests. It also restored natural disturbance regimes, reflooded peatlands, restored historical river courses, and expanded protected areas to 65.8% of the region. The Nature for Society scenario emphasised reduced land use intensity, sustainable forestry, organic agriculture, and participatory flood management, covering 14.4% of the area. The Nature as Culture scenario highlighted community stewardship, biodiversity-friendly agriculture such as paludiculture, and the reintroduction of culturally significant species, encompassing 8.6% of the area. All scenarios converged on restoring water dynamics and improving connectivity. Spatial mapping identified both unique and overlapping priority areas. Overlaps near natural parks, grasslands, and settlements created high-value mosaics that support biodiversity, water regulation, and cultural services. These areas offer opportunities for risk management, sustainable agriculture, and the restoration of ecosystem services. Incorporating stakeholder perspectives enabled the identification of synergies and conflicts, guiding the development of context-specific strategies. Integrating scenario planning with participatory mapping strengthens adaptive restoration planning and provides a replicable model. This approach aligns rewilding actions with ecological, social, and cultural objectives, delivering tangible benefits for biodiversity, local communities, and policy implementation.